Development and Pilot Testing of Standardized Food Images for Studying Eating Behaviors in Children - Kling, Samantha M. R.; Pearce, Alaina L.; Reynolds, Marissa L.; Garavan, Hugh; Geier, Charles F.; Rolls, Barbara J.; Rose, Emma J.; Wilson, Stephen J.; Keller, Kathleen L. (Frontiers in Psychology, 2020)
Food images are routinely used to investigate the cognitive and neurobiological mechanisms of eating behaviors, but there is a lack of standardized image sets for use in children which limits cross-study comparisons. To address this gap, we developed a set of age-appropriate images that included 30 high-energy-dense (ED) foods (>2.00 kcal/gram), 30 low-ED foods (<1.75 kcal/gram), and 30 office supplies photographed in 2 amounts (i.e. “larger” and “smaller”). Preliminary testing was conducted with children (6-10 years) to assess recognition, emotional valence (1=very sad, 5=very happy), and excitability (1=very bored, 5=very excited). After initial testing, 10 images with low recognition were replaced; thus, differences between Image Set 1 and Image Set 2 were analyzed. Thirty (n=30, mean age 8.3±1.2 years) children rated Set 1 and a different cohort of 29 children (mean age 8.1±1.1 years) rated Set 2. Changes made between image sets improved recognition of low-ED foods (Set 1=88.3±10.5% vs. Set 2=95.6±10.6%; P<0.0001) and office supplies (83.7±10.5% vs. 93.0±10.6%; P<0.0001). For the revised image set, children recognized more high-ED foods (98.4±10.6%) than low-ED foods (95.6±10.6%; P<0.05) and office supplies (93.0±10.6%; P<0.0001). Recognition also improved with age (P<0.001). Excitability and emotional valence scores were greater for high-ED foods compared to both low-ED foods and office supplies (P<0.0001 for both). However, child fullness ratings influenced the relationship between excitability/emotional valence and category of item (P<0.002). At the lowest fullness level, high-ED foods were rated highest in both excitability and emotional valence, followed by low-ED foods and then office supplies. At the highest fullness level, high-ED foods remained highest in excitability and emotional valence, but ratings for low-ED foods and office supplies were not different. This suggests that low-ED foods were more exciting and emotionally salient (relative to office supplies) when children were hungry. Ratings of recognition, excitability, and emotional valence did not differ by image amount. This new, freely available, image set showed high recognition and expected differences between image category for emotional valence and excitability. When investigating children’s responsiveness to food cues, specifically energy density, it is essential for investigators to account for potential influences of child age and satiety level.